Ethno-Cultural Identity of Northeast India with Reference to Temsula Ao’s Select Poems - Saranya Chandrasekaran; Sheela P Karthick; Rajakumar Guduru (TRANS-KATA: Journal of Language, Literature, Culture and Education, 2022)
Northeast part of India is known for its ethnogenic significance which has many roots of civilization, and it is distinct from the other part of the country. Therefore, the culture of Northeast India faces tremendous challenges due to its vast ethnographic diversity. Temsula Ao, is one of the most widely read and studied women writers of North-East India. She has been the recipient of many awards including the Padma Shri in 2007 and the Sahitya Akademi award in 2013.  She is also a pioneer writer from Nagaland. The main aim of this study is to explore ethno-cultural aesthetics of the Northeast Indian region which exists in Temsula Ao’s poetry. For that purpose, fifteen of her poems are selected from her anthology titled Books of Songs. The select poems were analysed qualitatively.  This descriptive qualitative research methodology deals how Ao-Naga regional people know about human values, beliefs, behavious, and social conditions within their own environmental contexts. The major finding of this paper is in what way Temsula Ao revitalizes Ao-Naga culture and tradition by picturising her region, history and condition of women relating them with nature through her poems. Implications were identified for the people of diverse cultural backgrounds. And, it is concluded that the beauty of a region is retained by the people who have a staunch belief in their traditional cultural values and ethics.